Оцінка і розвиток інноваційного потенціалу підприємства - Кучинський, Володимир Анатолійович; Гайдукова, А. Д. (НТУ "ХПІ", 2014)
Запропоновано підхід до оцінки та визначення напрямків розвитку інноваційного потенціалу підприємства, елементами якого є: визначення рівня основних складових та загальна оцінка рівня інноваційного потенціалу підприємства; використання бальної оцінки для визначення важливості кожного елементу у формуванні інноваційного потенціалу підприємства; використання SWOT- аналіз для визначення напрямків розвитку інноваційного потенціалу підприємства.

Innovative potential characterizes possibilities of any enterprise to carry out innovative activity complex. For this reason a management innovative potential is one of major tasks for any enterprise, in fact efficiency of activity at the market in the conditions of hard competitive activity depends foremost on possibility to grow and actively utillize organizational, technical, marketings and other innovative possibilities which make innovative potential. Offered approach to the estimation and determination of directions of development of innovative potential of enterprise the elements of which is: determination of level of basic constituents and general estimation of level of innovative potential of enterprise; the use of ball estimation is for determination of importance of every element in forming of innovative potential of enterprise; the use is a SWOT-analysis for determination of directions of development of innovative potential of enterprise.
Estimation and development of innovative potential of enterprise
Keywords: ефективність; SWOT-аналіз; кризові умови господарювання; рентабельність; innovative potential of enterprise; estimation; development; efficiency; SWOT-analysis